Penggunaan Bahasa Figuratif dan Leksikal pada Kumpulan Puisi Luka Kata Karya Candra Malik - Sari, Sonica Winda; Shomary, Sudirman (UIR PRESS, 2021)
Figurative language is a form of poetry in poetry. Figurative language is a form of language that has deviated from everyday language. In writing poetry, it is also related to lexical use or the choice of words used based on sound and meaning constancy considerations. The problems described in this study are (1) How is the use of figurative language in Candra Malik's collection of Word Wound poetry? (2) How is the use of the lexical contained in the collection of Word Wound poetry by Candra Malik? The objectives of this study are (1) Collect, describe, analyze and interpret in detail and systematically data and information so as to obtain an overview of the figurative language contained in the collection of Word Wound poetry by Candra Malik (2) Collect, describe, analyze and interpret in detail and systematically the data and information so as to obtain a lexical description contained in the collection of word wound poetry by Candra Malik. The theory that the writer uses to analyze this research is the theory of Nurgiyantoro (2014), Wiyatmi (2012), Hasanudin (2012). The approach used is a qualitative approach. The type of research used is library research (Library Research). The method used is descriptive method. The technique used is the hermeneutic technique. The results of the study the authors concluded that the use of figurative language contained 32 data and lexical use there were 21 data. The use of figurative language that often appears in Candra Malik's Word Wound poetry is the form of comparative figure of speech and the most dominant is simile, while the use of lexical is sound determination.